The role of education, knowledge and human resources for the agricultural development in the perspective of new cap: an hypothesis of change in Basilicata - Contò , F.; Fiore , M.; La Sala, P.; Papapietro , P. (Applied Studies in Agribusiness and Commerce, 2012)
The role of education, knowledge and human resources in the agribusiness becomes of primary importance for the development of agricultural sector and, more generally, of the territory. The main objective of the present paper is to verify the role of investment in human resources and, consequently, in services for the agricultural development for the dynamics of rural development, trade and international cooperation of agribusiness.After a literature review, the paper firstly analyses the characteristics of the Italian Region of Basilicata, selected for our empirical application, and secondly develops an econometric model to explain the relationship between the rural GDP and a set of economic variables and of network-education-social (NES) dummy variable. These NES is representative of social, educational and, network factors, describing the degree of openness of the region firm. As expected, the results show that farmers may act as engines for economic development when they are trained on the basis of the needs and requirements related to innovation and research, and they are assisted through new models of organization of agricultural services.